High-Pressure Processing of Reduced Salt Pangasius Catfish (Pangasianodon hypophthalmus) Minced Muscle: The Effects on Selected Quality Properties of Its Gels - Binh Q. Truong; Roman Buckow; Kha N. H. Nguyen; Linh T. Nguyen; Tuan N. A. Huynh; Van Chuyen Hoang (Applied Sciences)
This study investigated the effects of high-pressure processing (HPP) on selected physicochemical properties of pangasius gels at reduced salt concentrations. Minced pangasius muscle was treated at different HPP conditions (300–500 MPa/10 °C/10 min) with 1% or 2% added salt, then cooking (90 °C/30 min) and compared to heat-induced gels (HIGs) with 2% added salt and cooking (90 °C/30 min). The results showed that HPP significantly improved the texture, whiteness, and water-holding capacity of gels added salt 2% as compared to HIGs. At a reduced salt concentration of 1%, the gel texture, whiteness, and water-holding capacity of pangasius gels are similar to HIGs. SDS-PAGE showed a reduction in myosin band intensity of both SDS-soluble and sarcoplasmic proteins with pressure treatment. Sarcoplasmic actin protein was undetectable in all treatments. Fourier transform infrared spectroscopy (FTIR) analysis revealed higher α-helix content in HPP-treated samples, while SEM images confirmed the formation of a denser, more uniform gel network, particularly at 2% salt. These findings suggested that HPP improved the quality of gel with 2% salt added, while producing gels with similar quality compared to HIGs at reduced salt concentration.